2015
DOI: 10.3835/plantgenome2014.07.0031
|View full text |Cite
|
Sign up to set email alerts
|

Marker‐Assisted Backcrossing to Develop an Elite Cytoplasmic Male Sterility Line in Rice

Abstract: Cytoplasmic male sterility (CMS) is a cornerstone of hybrid production in many crops. In three-line hybrid systems, use of CMS, maintainer, and fertility restorer lines is necessary for production of hybrid seeds. Limited resources of CMS and low variation of CMS lines cause genetic vulnerability to pathogens. Therefore, diversifying the CMS sources is indispensible for a sustainable production system of hybrid seed. In this study, we attempted for the first time to transfer CMS into maintainer line Yosen B in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Similar to the findings of the present study, Ahmadikhah et al, (2015) had identified 43polymorphic SSR markers by using 100 SSR markers with 30 per cent polymorphism in IR68897A, maternal CMS donor and Yosen B line, which is a potential maintainer line. Whereas Raghvendra and Hittalmani (2018) used 96 polymorphic SSR marker to develop a potential male sterile line for the production of promising hybrids suitable for aerobic conditions with 44% parental polymorphism.…”
Section: Resultssupporting
confidence: 86%
“…Similar to the findings of the present study, Ahmadikhah et al, (2015) had identified 43polymorphic SSR markers by using 100 SSR markers with 30 per cent polymorphism in IR68897A, maternal CMS donor and Yosen B line, which is a potential maintainer line. Whereas Raghvendra and Hittalmani (2018) used 96 polymorphic SSR marker to develop a potential male sterile line for the production of promising hybrids suitable for aerobic conditions with 44% parental polymorphism.…”
Section: Resultssupporting
confidence: 86%
“…Evaluation of important traits with direct or indirect effect on grain yield and sustainability of rice growers is indispensable for successful breeding of rice. Estimation of genetic parameters helps our understanding about gene action, identification of components of genetic variances and, finally facilitates the selection of a desirable breeding method (Ahmadikhah et al, 2007, Immanuel et al, 2013Ahmadikhah et al, 2015). The knowledge of genetic variability present in a given crop species for the character under improvement is of paramount importance for the success of any plant breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…In a CMS system, several cycles of backcrossing are required to develop sterile “A-line” versions of the female inbred lines. In early backcrossing generations, the A-lines still contain significant amounts of donor genome and do not accurately reflect the B-line genotype (Ahmadikhah et al 2015). Neither is necessarily a major concern for production of commercial seed, where CHA applications can be optimized for each commercial hybrid and there is enough time for as many cycles of backcrossing as necessary to remove nearly all residual donor genome.…”
Section: Discussionmentioning
confidence: 99%